Kodak "Bubble" Theater (Seville Enterprises, Inc.)
Eastman Kodak air-supported "bubble" theater seats 200 fair-goers for a movie on environment. The theater, of plastic-impregnated fabric, is adjoined by a diamond-shaped structure in which the Expo visitors can await entrance to the movie. Experts will advise fair-goers on their photography questions. The exhibit occupies 4,000 square feet.